Testing Witness Testimony According to the Criminal Code and Qanun - Kaswandi; Hayun; Muh Sutri Mansyah (PT Justitia Legal Research, 2025)
Witnesses who testify in court are required to speak the truth; however, there are also instances where witnesses provide false testimony. The challenges of implementing Articles 291 and 373 of the current Indonesian Criminal Code (KUHP) and Article 170 of the Aceh Qanun in prosecuting witnesses who give false testimony are important to examine and analyze. This research uses a normative method with legislative, historical, conceptual, and futuristic approaches. The analytical techniques employed in this study are descriptive and prescriptive. Legal materials are analyzed by evaluating the collected data. The interpretation methods used are systematic and grammatical. The findings of this study show that the primary objective of Articles 291 and 373 of the current Indonesian Criminal Code and Article 170 of the Aceh Qanun is to ensure that witnesses provide truthful testimony in court based on what they have seen, experienced, or heard, whether directly or indirectly. However, challenges also arise in prosecuting witnesses who give false testimony. There is potential for multiple interpretations because neither Articles 291 and 373 of the Criminal Code nor Article 170 of the Aceh Qanun specify how many times a witness must give false testimony before these articles can be applied, or whether a single instance of false testimony is sufficient for the application of these articles. This creates the potential for judges to apply these articles subjectively. Therefore, future legislation by the government and lawmakers must establish clear benchmarks for determining when a witness has provided false testimony.